2011
DOI: 10.1021/nn200276a
|View full text |Cite
|
Sign up to set email alerts
|

Salt-Mediated Self-Assembly of Thioctic Acid on Gold Nanoparticles

Abstract: Self-assembled monolayer (SAM) modification is a widely used method to improve the functionality and stability of bulk and nanoscale materials. For instance, the chemical compatibility and utility of solution-phase nanoparticles are often improved using covalently bound SAMs. Herein, solution-phase gold nanoparticles are modified with thioctic acid SAMs in the presence and absence of salt. Molecular packing density on the nanoparticle surfaces is estimated using X-ray photoelectron spectroscopy and increases b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
102
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(112 citation statements)
references
References 111 publications
(196 reference statements)
6
102
0
1
Order By: Relevance
“…The gold nanoparticles capped and stabilized with thiol-derivative monolayers are dispersed in organic solvents [7,10]. Since then enormous researches have been performed on modifying the surface of gold colloids through changing the molecular structures of the thiolates on the particle surface [11][12][13][14][15][16][17]. The protection capping agent (thiols) is chemically bound to the surface of gold nanoparticles [7].…”
Section: Introductionmentioning
confidence: 99%
“…The gold nanoparticles capped and stabilized with thiol-derivative monolayers are dispersed in organic solvents [7,10]. Since then enormous researches have been performed on modifying the surface of gold colloids through changing the molecular structures of the thiolates on the particle surface [11][12][13][14][15][16][17]. The protection capping agent (thiols) is chemically bound to the surface of gold nanoparticles [7].…”
Section: Introductionmentioning
confidence: 99%
“…Under low ionic strength conditions, the monolayer of our NP scaffolds should acquire a lower compaction degree. 20,21 All NPs scaffolds displayed increased substrate adsorption capacity in deionized water than PBS (see ESI-4). These results suggest that the more expanded the monolayer of our NPs the greater their capacity to associate substrates (see ESI-5).…”
Section: Resultsmentioning
confidence: 99%
“…1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 reconciled with the results of XPS studies of lipoic acid based SAMs which almost always show both 'bound' (Au?S) and 'unbound' (S?H or S?S) sulfur. 31,32 The source and nature of the 'unbound' sulfur revealed by these XPS studies remains unclear. It has been suggested that, for lipoic acid itself, it relates to an ionically bound or hydrogen bonded ad?layer on top of the lipoic acid SAM.…”
Section: And/mentioning
confidence: 99%